2012
DOI: 10.7314/apjcp.2012.13.12.5989
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Re-participation in Faecal Occult Blood Test-Based Screening for Colorectal Cancer

Abstract: Background: There is little information on longitudinal patterns of participation in faecal occult blood test (FOBT) based colorectal cancer (CRC) screening or on demographic or behavioural factors associated with participation in re-screening. The lack of an agreed system for describing participatory behaviour over multiple rounds also hampers our ability to report, understand and make use of observed associations. Our aims were to develop a system for describing patterns of participatory behaviour in FOBT-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…Less than half reported that had ever received a physician recommendation for screening or been given an FOBT kit - two of the strongest determinants of screening completion [16,36,40–45]. In each of the study arms patients were given a recommendation for screening and an FOBT kit by study staff.…”
Section: Discussionmentioning
confidence: 99%
“…Less than half reported that had ever received a physician recommendation for screening or been given an FOBT kit - two of the strongest determinants of screening completion [16,36,40–45]. In each of the study arms patients were given a recommendation for screening and an FOBT kit by study staff.…”
Section: Discussionmentioning
confidence: 99%
“…16 Population-based screening programs abroad, where FOBTs are mailed from a country’s centralized public health service, have documented higher repeat FOBT screening rates (39% to 55%). 43–46 …”
Section: Discussionmentioning
confidence: 99%
“…Population based screening programs abroad where FOBTs are mailed by centralized health service to eligible individuals have higher repeat FOBT screening rates (39% to 55%) [24-27]. Interestingly, in these programs which eliminate geographic and cost barriers completion rates were lower in individuals from rural areas and those of lower socioeconomic status [28].…”
Section: Introductionmentioning
confidence: 99%